(3YfhGf GdoeQbUGJ hGdoeWQHGJs - (3Ydj Hf ehSi Hf eMeO Hf YHO Gdedc GHf SYjO, GdYfSj GdeOdLj GdeZQHj , CHh GdMSf, fhQ GdOjf,J (B685 (3g` s
(3ChdgG (B:s
(3CeG HYO MeO Gddg GdPj TQa GdEfSGf, Ydi SGFQ CfhGY GdMjhGf HfWb GddSGf s
(3BNQgG (B:s
(3YLHJ dg hgh GdCUjd HYQag XdGe hHjf GdfGXQjf UHGM JeJ GdeQbUGJ hGdeWQHGJ hGdMeO ddg s
(3ChQGbgG eVWQHI GdJQJjH aj GdOGNd GfXQ hQbI (B38 (3heG HYOgGs
(3JJab aj ChdgG eY GdfSNI GdChdi HGNJdGa aj HYV GdCdaGX hJNJda aj BNQgG CMjGfkGs
(3fSNI KGfjIs
(3hChdgG JedjcGJ CbOegG YGe (B1164(3g`s
(3hHgG fXGe GdJYbjHI s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs